A secure and efficient password‐authenticated group key exchange protocol for mobile ad hoc networks. (24th October 2011) - He, Daojing; Chen, Chun; Ma, Maode; Chan, Sammy; Bu, Jiajun
SUMMARY Password‐authenticated group key exchange protocols enable communication parties to establish a common secret key (a session key) by only using short secret passwords. Such protocols have been receiving significant attention. This paper shows some security weaknesses in some recently proposed password‐authenticated group key exchange protocols. Furthermore, a secure and efficient password‐authenticated group key exchange protocol in mobile ad hoc networks is proposed. It only requires constant round to generate a group session key under the dynamic scenario. In other words, the overhead of key generation is independent of the size of a total group. Further, the security properties of our protocol are formally validated by a model checking tool called AVISPA. Security and performance analyses show that, compared with other related group key exchange schemes, the proposed protocol is also efficient for real‐world applications in enhancing the security over wireless communications. Copyright © 2011 John Wiley & Sons, Ltd.